A molecular dynamics approach to the interfacial characteristics between melamine formaldehyde resin and paving asphalts. (15th February 2023) - Dan, Han-Cheng; Wen, Xiang; Chen, Jiaqi; Cao, Wei; Jing, Hualong
Highlights: A comprehensive evaluation method was proposed for the interfacial characterization. A clear boundary was noted between melamine formaldehyde (MF) and the asphalts. MF achieved better blending with the neat asphalt than with the polymer modified. Addition of MF enhanced the diffusion of all components in both asphalts. Abstract: Various microencapsulation technologies involving different shell and core materials have been proposed in the literature for improving the asphalt mixture performance. The interfacial characteristics including adhesion between the microcapsule shell and asphalt largely determines the synergistic rheology of the blend. This study evaluated the impacts of melamine formaldehyde (MF) resin as the shell material on the interface and bulk properties of a neat and styrene–butadienestyrene (SBS) modified asphalt binders using the techniques of scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and molecular dynamics (MD) simulation. The clear interface without voids or cracks revealed in the SEM images suggested good adhesion between MF and both asphalts. Satisfactory interfacial binding was also suggested in the FT-IT results. The absorption peak strength of the neat asphalt was higher than that of SBS modified asphalt, and the binding of MF with neat asphalt was stronger than with the modified. The modified asphalt exhibited a slightly lower compatibility due to the high difference in the solubility parameter between SBS and MF, 9.783(J/cm −3 ) 0.5 . Introduction of MF promoted self-association of the asphaltenes and enhanced the diffusion of all the four fractions in both asphalt systems. Diffusion of the asphaltenes in the neat and modified asphalts saw the highest enhancement, which was increased to 5.3915 and 3.7893 (10 -10 m 2 s −1 ), respectively. Increase in diffusion coefficient was attributed to the high polarity and mobility of the MF molecules.